PENGARUH PEMBERIAN EDUKASI PEMERIKSAAN PAYUDARA SENDIRI (SADARI) TERHADAP PENINGKATAN PENGETAHUAN REMAJA PUTRI DALAM DETEKSI DINI KANKER MAMMAE DI SMA NASIONAL MAKASSAR - Sugarni, Mika (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Breast cancer, also called mammary cancer, is the uncontrolled growth of breast cells due to abnormal changes in genes that play a role in cell division. Early detection is a very important first step to find out early the presence of tumours or lumps in the breast so as to reduce the death rate due to cancer. The high incidence of mammary cancer is due to the lack of awareness in women to conduct early detection of the breast if they experience abnormalities such as lumps. Health education is an effort to improve one's health knowledge and prevent disease. Objective: To determine the effect of providing education (SADARI) on increasing the knowledge of adolescent girls in early detection of mammary cancer. The method used in this study was to use a quasi experiment approach with one group pre-test and post-test design. Sampling by total sampling with a sample size of 60 respondents. Data collection was carried out using a questionnaire. Data management using SPSS. The analysis used was univariate analysis and bivariate analysis using the Wilcoxon test (? <0.05). The results of bivariate analysis showed that there was an effect of providing SADARI education with a value of (? = 0.000). It can be concluded that there is an effect of providing education on breast self-examination (SADARI) on increasing the knowledge of adolescent girls in early detection of mammary cancer at Makassar National High School.